1987
DOI: 10.1111/j.1365-2885.1987.tb00089.x
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacodynamics of the flukicidal salicylanilides, rafoxanide, closantel and oxyclosanide

Abstract: The pharmacokinetics of oxyclosanide, rafoxanide and closantel were investigated in sheep (n = 5). All three drugs were extensively (greater than 99%) bound to plasma proteins and the plasma concentration/time curve was best described by a tri-exponential equation. Closantel and rafoxanide had long terminal half-lives (mean 14.5 and 16.6 days, respectively) compared with oxyclosanide (mean 6.4 days). In a study of the efficacy of rafoxanide against Fasciola hepatica, a dose rate of 7.5 mg kg-1 against 6-week-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 16 publications
2
26
1
Order By: Relevance
“…The ability of younger rats to eliminate the drug faster will reduce the fluke's exposure to the drug and so limit the disruption caused, an effect which was seen in the present study. Liver fluke infection is known to reduce the host's ability to metabolise xenobiotics, including anthelmintics such as nitroxynil, oxyclozanide and rafoxanide (Maffei Facino et al 1984Mohammed-Ali and Bogan 1987; see also review by Behm and Sangster, 1999). Age-related changes in the host's drug-metabolising capacity have also been described in sheep following netobimin administration (McKellar et al 1995).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The ability of younger rats to eliminate the drug faster will reduce the fluke's exposure to the drug and so limit the disruption caused, an effect which was seen in the present study. Liver fluke infection is known to reduce the host's ability to metabolise xenobiotics, including anthelmintics such as nitroxynil, oxyclozanide and rafoxanide (Maffei Facino et al 1984Mohammed-Ali and Bogan 1987; see also review by Behm and Sangster, 1999). Age-related changes in the host's drug-metabolising capacity have also been described in sheep following netobimin administration (McKellar et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Inset shows a higher power image of the exposed basal lamina (bl) posterior to the ventral sucker. Bar 5 lm Michiels et al 1987;Mohammed-Ali and Bogan 1987;Hennessy et al 1989;Alvinerie et al 1991). This opens up the possibility of oral ingestion of these compounds as well.…”
Section: Discussionmentioning
confidence: 98%
“…Because of its haematophagous behaviour as an adult, F. hepatica is particularly susceptible to drugs which bind to plasma proteins. Several fasciolicides bind to such proteins: the salicylanilides, closantel, rafoxanide and oxyclozanide; the halogenated phenol, nitroxynil; and the benzimidazole derivative, triclabendazole (Mohammed Ali et al 1986;Hennessy et al 1987;Michiels et al 1987;Mohammed-Ali and Bogan 1987;Alvinerie et al 1991aAlvinerie et al , 1991b. Consequently, it is probable that they enter the fluke predominantly via the mouth, that is by oral ingestion.…”
Section: Introductionmentioning
confidence: 96%
“…Although the drug has been in use over a long period, there have been few reports on its pharmacokinetics or methods of assay. Mohammed-A1 i and Bogan (1) recently reported that rafoxanide had a half life of 17 days in the plasma of sheep and that it was extensively bound to plasma proteins. They determined the half life value from plasma rafoxanide levels following oral administration of the normal therapeutic dose of 7.5 mg kg-I bodyweight.…”
Section: Rafoxanide (35-diiodo-3'-chloro-4'-[p-chlorophenoxy]mentioning
confidence: 98%